2018
DOI: 10.1007/s00284-018-1563-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bacillus velezensis NJAU-Z9 Enhanced Plant Growth Associated with Efficient Rhizospheric Colonization Monitored by qPCR with Primers Designed from the Whole Genome Sequence

Abstract: Plant growth-promoting rhizobacteria (PGPR) have been reported to influence plant growth, yield, and nutrient uptake by an array of mechanisms. Uncovering the behavioral dynamics of PGPR is one of the most important issues necessary for understanding their functional performances. In this study, strain NJAU-Z9 which was found to possess complex functions and efficient rhizospheric colonization ability was selected from plenty of bacterial strains isolated randomly from the pepper rhizosphere soil and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The improved growth performance in the Asiatic lilium hybrids 'Tresor' upon inoculation of Lle-9 might be due to the growth-promoting effects as were evaluated through several qualitative and quantitative tests. Previous studies also reported similar growth improvement when plants were inoculated with the isolated strains of Bacillus velezensis [75,40]. The isolated B. velezensis strain Lle-9 showed antagonistic effects against the broad-spectrum fungal pathogens.…”
Section: Discussionsupporting
confidence: 59%
“…The improved growth performance in the Asiatic lilium hybrids 'Tresor' upon inoculation of Lle-9 might be due to the growth-promoting effects as were evaluated through several qualitative and quantitative tests. Previous studies also reported similar growth improvement when plants were inoculated with the isolated strains of Bacillus velezensis [75,40]. The isolated B. velezensis strain Lle-9 showed antagonistic effects against the broad-spectrum fungal pathogens.…”
Section: Discussionsupporting
confidence: 59%
“…In particular, PGPB exerts beneficial effects on plant growth through several ways: facilitating the acquisition of soil nutrients by asymbiotic N 2 -fixation and inorganic P and K solubilization; modulating the level of phytohormone such as indole-acetic acid (IAA), cytokinins, and gibberellins (GA3); resisting against phytopathogen [1]. At present, majority of field-tested bacterial taxonomic groups affiliated to PGPB belonged to ranges of genera: Azospirillum, Rhizobium, Agrobacterium, Rhizobium (Alphaproteobacteria); Azoarcus, Burkholderia, (Betaproteobacteria); Acinetobacter, Enterobacter, Klebsiella, Pantoea, Pseudomonas, Serratia, (Gammaproteobacteria); Bacillus, Frankia (gram-positive bacteria) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Capsicum annuum L. The soil amended with Bacillus velezensis improves seedling height, stem diameter, and yields compared to those pepper plants grown on un-amended soil [37] Arabidopsis thaliana…”
Section: Impact Of Rhizobacteria On the Plant Referencementioning
confidence: 99%